Violence, Coercion And Escalation In Contemporary Strategic Competition - Banasik, Mirosław (Roczniki Nauk Społecznych, 2024)
The purpose of the research was to clarify and characterize the meaning of violence, coercion and escalation in contemporary strategic competition. The main research problem was articulated with the question: in what is violence, coercion and escalation expressed and characterized in contemporary strategic competition? The research process used literature analysis and criticism, non-participatory observation and case studies. As a result of the research, it was established that violence and coercion are always present in strategic competition. They are specific tools of international influence to achieve specific political goals. Coercion is the use of force in a limited way, a demonstration of force, or the use of armed force and the conduct of an armed clash. Coercion includes deterrence and forcing. Escalation is an increase in the intensity or scope of a dispute or conflict between two parties that exceeds a threshold considered significant by one or more of its participants. Escalation is an interactive phenomenon that occurs between two (or more) parties to a conflict who seek unilateral advantage. Escalation is prevented by strategic deterrence or by having escalatory dominance.